Archelosaurian Color Vision, Parietal Eye Loss, and the Crocodylian Nocturnal Bottleneck. (26th December 2016) - Emerling, Christopher A.
Abstract : Vertebrate color vision has evolved partly through the modification of five ancestral visual opsin proteins via gene duplication, loss, and shifts in spectral sensitivity. While many vertebrates, particularly mammals, birds, and fishes, have had their visual opsin repertoires studied in great detail, testudines (turtles) and crocodylians have largely been neglected. Here I examine the genomic basis for color vision in four species of turtles and four species of crocodylians, and demonstrate that while turtles appear to vary in their number of visual opsins, crocodylians experienced a reduction in their color discrimination capacity after their divergence from Aves. Based on the opsin sequences present in their genomes and previous measurements of crocodylian cones, I provide evidence that crocodylians have co-opted the rod opsin (RH1) for cone function. This suggests that some crocodylians might have reinvented trichromatic color vision in a novel way, analogous to several primate lineages. The loss of visual opsins in crocodylians paralleled the loss of various anatomical features associated with photoreception, attributed to a "nocturnal bottleneck" similar to that hypothesized for Mesozoic mammals. I further queried crocodylian genomes for nonvisual opsins and genes associated with protection from ultraviolet light, and found evidence for gene inactivation or loss for several of these genes. Two genes, encoding parietopsin and parapinopsin, were additionally inactivated in birds and turtles, likely co-occurring with the loss of the parietal eye in these lineages.